1658a Experiences and lessons learnt in the preparation of lists of occupational diseases and of the related diagnostic criteria. (24th April 2018) - Colosio, C
Abstract : According to ILO, an occupational disease is 'Any disease contracted as a result of an exposure to risk factors arising from work activity'. In most countries, a disease is defined 'occupational' when the national authorities acknowledge its occupational origin. The main tool available to national authorities to recognise the occupational origin of a disease are the lists, but aims, contents, structure and size of the lists significantly vary, from countries which have not any list to countries having lists composed of more than hundred groups of occupational diseases, therefore harmonisation is needed. A disease can be included in a list when the evidence of its link with exposure is strong, and solid diagnostic criteria exist. The main points for definition of diagnostic criteria are clinical features, occupational history and exposure, natural history and progress of the disease, and differential diagnosis. Other parameters are the minimum intensity of the exposure necessary to cause the disease and its minimum duration, the maximum latent period, that is the maximum time that can elapse from the induction or, as surrogate, from the beginning of exposure to the onset of the disease. Finally, the criteria of a minimum induction and the maximum disease-free period (from the end of the exposure to the onset of the disease) should be fulfilled. Unfortunately, these criteria cannot be guaranteed in condition mainly 'symptom based', such as low back pain, migraine, burnout, Karoshi. Also new diseases, diseases emerging from new risks or from new presentations of know risks deserve attention. Finally, the main properties of 'good' lists and criteria are credibility (involvement of experts and availability of references), consensus (among experts, employers, employees and governments), and consistency. These criteria and needs have been considered in the preparation of the document 'International Guidance Notes on the Diagnostic Criteria of Occupational Diseases'.